European Universities in the Aftermath of the Economic Crisis - Ritzen, Jo (International Higher Education, 2016)
European universities have suffered from the economic crisis over the period 2008-2014. In the countries hardest hit, future university graduates are likely to be less competent, while a reduced research performance. Europe as a whole has lost some of its competitive edge versus Asia even though equality of opportunity has been safeguarded.